Exploring how teacher-related factors relate to student achievement in learning advanced algebra in technology-enhanced classrooms. - Hegedus, Stephen; Tapper, John; Dalton, Sara (Journal of Mathematics Teacher Education, 2016)
In this study, we examine the relationship between contextual variables related to teachers and student performance in Advanced Algebra classrooms in the USA. The data were gathered from a cluster-randomized study on the effects of SimCalc MathWorlds®, a curricular and technological intervention as a replacement for Algebra 2 curriculum, on student learning of Algebra 2 content. Conditional measures (teacher background characteristics) and instructional measures (self-reported instructional preferences, stances, and classroom practices) were subjected to a variety of empirical analyses to discern their relationship to student learning. Researchers examined both the overall effect of teacher contextual variables on student learning and the specific effect of SimCalc on both teacher instructional measures and student performance. There is evidence to support that teachers who use the SimCalc curriculum value classroom communication, deep understanding of math concepts, and support for both routine and non-routine problems. © Springer Science+Business Media Dordrecht 2014.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-412-463-374-521 tex.type: [object Object]
Keywords: Algebra; Connectivity; Dynamic representations; Student achievement; Teacher contextual variables; dept.edu

Intuitive thinking and misconceptions of independent events: a case study of us and french pre-service teachers - Nabbout-Cheiban, Marie (International Journal of Research in Undergraduate Mathematics Education, 2016)
In this article we study the conceptions of an American and a French group of undergraduate pre-service teachers regarding the concept of independent events. Specifically, we study the role that intuition plays in their answers, ascertain the presence of probabilistic biases, and compare the findings with previous results collected on a different population. Participants were asked to provide essay-type answers to a three-part questionnaire that asked them to solve problems, react to hypothetical students’ answers, and answer direct questions. The concept of independent events was problematic for most participants as was the distinction between mutually exclusive and independent events. In addition, representativeness bias and the Falk Phenomenon were observed among several participants.
5 citations (Crossref) [2023-10-31]
Keywords: dept.edu